Plasma Interleukin-6 Level: A Potential Prognostic Indicator of Emergent HBV-Associated ACLF - Zhe-Bin Wu; Yu-Bao Zheng; Ke Wang; Zhi-Shuo Mo; Xu Zhen; Ying Yan; Zhi-Liang Gao (Canadian Journal of Gastroenterology and Hepatology)
Objective. To identify markers that predict the progression to hepatitis B virus-associated acute-on-chronic liver failure (HBV-ACLF). Methods. We recruited 125 patients with chronic hepatitis B (CHB) between September 2013 and March 2017. During hospitalization, 25 patients progressed to LF and were classified as the LF group, while the remaining 100 patients were classified as the non-LF (NLF) group. We compared the kinetic changes in clinical and immune indicators including age, total bilirubin level, prothrombin time, model for end-stage liver disease score, interleukin (IL)-6, IL-8, and IL-10 cytokine levels, and number of T helper 17 and regulatory T cells between groups to determine their association with progression to HBV-ACLF. The prognostic value of clinical and immune indicators was determined using the area under the receiver operating characteristic curve (AUC) value. Results. Cox regression analysis suggested that the plasma IL-6 level could predict CHB progression to HBV-ACLF (relative risk = 1.082, 95% confidence interval: 1.006–1.164; P=0.034). The AUC value, sensitivity, and specificity of baseline IL-6 level for predicting HBV-ACLF were 82.63%, 83.3%, and 82.9%, respectively (P=0.001). Conclusion. A high plasma IL-6 level in CHB patients could be an early biomarker for HBV-ACLF.